2014
DOI: 10.1017/s1473550414000081
|View full text |Cite
|
Sign up to set email alerts
|

The Mt John University Observatory search for Earth-mass planets in the habitable zone of α Centauri

Abstract: The 'holy grail' in planet hunting is the detection of an Earth-analogue: a planet with similar mass as the Earth and an orbit inside the habitable zone. If we can find such an Earth-analogue around one of the stars in the immediate solar neighbourhood, we could potentially even study it in such great detail to address the question of its potential habitability. Several groups have focused their planet detection efforts on the nearest stars. Our team is currently performing an intensive observing campaign on t… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
25
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
4
4
1

Relationship

1
8

Authors

Journals

citations
Cited by 48 publications
(25 citation statements)
references
References 43 publications
0
25
0
Order By: Relevance
“…Moreover, a ground-based radial velocity campaign has ruled out the presence of very massive close-in planets (Endl et al 2015) and Plavchan et al (2015) have shown that a <3.3 Earth mass planet in a ∼3 day orbit (assuming that the Dumusque et al 2012 discovery is robust) would be stable when including the effects of tides and General Relativity. These factors, combined with the advances in computing hardware that enable much larger numerical simulations, motivate us to build upon the work of WH97 and perform long-duration integrations over a high-resolution grid in initial orbital parameters to determine the limits to the regions in this system where planetary orbits are stable on gigayear timescales.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, a ground-based radial velocity campaign has ruled out the presence of very massive close-in planets (Endl et al 2015) and Plavchan et al (2015) have shown that a <3.3 Earth mass planet in a ∼3 day orbit (assuming that the Dumusque et al 2012 discovery is robust) would be stable when including the effects of tides and General Relativity. These factors, combined with the advances in computing hardware that enable much larger numerical simulations, motivate us to build upon the work of WH97 and perform long-duration integrations over a high-resolution grid in initial orbital parameters to determine the limits to the regions in this system where planetary orbits are stable on gigayear timescales.…”
Section: Introductionmentioning
confidence: 99%
“…We note that it has recently become possible to modify planet-search Doppler codes to obtain precise velocities for SB2s, by including the secondary star's spectrum in the modelling process if the flux ratio is known. This novel approach is now being applied to the Alpha Centauri binary system Endl et al 2015). 749 944 5873 4696 5877 4618 20035 14868 31860 23061 46122 31118 58540 35790 76321 43772 81410 46159 98579 55374 136905 73525 137164 75689 142384 78027 153438 83224 176650 93383 176794 94208 204203 105953 A further 31 stars in the PPPS sample show large-amplitude velocity variations or long-term trends, which indicate stellar-mass companions.…”
Section: Introductionmentioning
confidence: 99%
“…We note that it has recently become possible to modify planet-search Doppler codes to obtain precise velocities for SB2s, by including the secondary star's spectrum in the modelling process if the flux ratio is known. This novel approach is now being applied to the Alpha Centauri binary system Endl et al 2015). …”
mentioning
confidence: 99%
“…There is at least one exoplanet discovered so far in this system -Proxima b (Anglada-Escudé et al 2016). Gas giant, Jupiter-like planets are concluded to be incompatible with the present measurements (Endl et al 2015). Proxima b is an excellent candidate for first-time exoplanet surface imaging.…”
Section: Proxima B and The Alpha Centauri Systemmentioning
confidence: 58%